Changing migrant spaces and livelihoods: Hostels as community residential units, Kwa-Mashu KwaZulu-Natal South Africa - Xulu, Nomkhosi (Department of Sociology, 2015)
This study focuses on the significance of the changes that are currently taking place at the KwaMashu hostel, the conversion of the hostel system and the transformation of migrant spaces and livelihoods. I trace the stories of hostel dwellers and the processes that take place when former single sex workers' hostels of the apartheid era are turned into Community Residential Units (CRUs). CRUs are family housing that has been designed by the government to replace workers' hostels. This thesis examines the sociology of the everyday life struggles of the migrants who live in CRUs. The "units" and the people who reside in them constitute the primary unit of analysis. Their families and social networks constitute the secondary unit of analysis. The CRUs are a significant site for the exploration of the redefinition of rural-urban connections in our society; connections which originate from the stubborn survival of migrancy as a key form of livelihoods procurement among large numbers of African working-class people.